2021
DOI: 10.1111/obr.13186
|View full text |Cite
|
Sign up to set email alerts
|

The impact of, and views on, school food intervention and policy in young people aged 11–18 years in Europe: A mixed methods systematic review

Abstract: Summary Understanding the social and environmental influencers of eating behaviours has the potential to improve health outcomes for young people. This review aims to explore the effectiveness of school nutrition interventions and the perceptions of young people experiencing a nutrition focused intervention or change in school food policy. A comprehensive systematic search identified studies published between 1 December 2007 to 20 February 2020. Twenty‐seven studies were included: 22 quantitative studies of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 71 publications
(354 reference statements)
0
25
0
Order By: Relevance
“…Characteristics of the 13 included reviews overall (i.e., all primary studies reported in the review irrespective of study design and other study characteristics) are described in Table 1. Of these, two reviews synthesised results for nutrition education interventions [26,44], three for food environment interventions interventions [24,25,45], one for HPS nutrition interventions [22], and seven synthesised other types of nutrition interventions [20,21,23,[28][29][30]46]. Included reviews were published between 2011 and 2021.…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of the 13 included reviews overall (i.e., all primary studies reported in the review irrespective of study design and other study characteristics) are described in Table 1. Of these, two reviews synthesised results for nutrition education interventions [26,44], three for food environment interventions interventions [24,25,45], one for HPS nutrition interventions [22], and seven synthesised other types of nutrition interventions [20,21,23,[28][29][30]46]. Included reviews were published between 2011 and 2021.…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%
“…The number of primary studies included within reviews ranged from 10 to 100. Of the 13 reviews, three reviews restricted the inclusion criteria for country, and one review each included only primary studies from developed countries [44], the United Kingdom (UK) and Europe [29], and middle-income countries [30]. Eleven reviews focused on interventions conducted solely in school-based settings [20][21][22]24,25,[28][29][30][44][45][46], and two reviews included interventions conducted across multiple settings (e.g., school, home, community), where results for the school setting were reported separately [23,26].…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating whole systems approaches and multilevel interventions in schools to promote healthy eating has been associated with increased healthy food choices (Townsend & Foster, 2013). Prioritising healthy food provision and nutrition education as a consistent part of the school agenda can have a positive impact on children and young people's wellbeing, learning and academic performance (Rose et al, 2021; WHO, 2006), whilst addressing food insecurity (Defeyter & Mann, 2020).…”
Section: Introductionmentioning
confidence: 99%